2023
DOI: 10.1111/1749-4877.12733
|View full text |Cite
|
Sign up to set email alerts
|

Antifertility effects of quinestrol in male lesser bandicoot rat, Bandicota bengalensis, and potential in managing rodent population under field conditions

Abstract: Integrating fertility control techniques using steroid hormones after lethal control can help reduce post control rebuildup of rodent populations. The current study is the first to assess the antifertility effects of quinestrol in male lesser bandicoot rat, Bandicota bengalensis which is the predominant rodent pest species in Southeast Asia. Rats in different groups were fed bait containing 0.00%, 0.01%, 0.02%, and 0.03% quinestrol for 10 days in laboratory and evaluated immediately, and 15, 30, and 60 days af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…Liu J. et al's results reflect the need to directly assess the response of a species to a control agent that has been tested in several other species (Jacoblinnert et al 2022;Massei et al 2023). Sidhu and Singla (2023) showed that the consumption of quinestrol alone for 10 days by male lesser bandicoot rats, Bandicota bengalensis, in the laboratory reduced their fertility for more than 30 days, with partial reversibility by 60 days. A small-scale field assessment yielded promising results but further, more broad-scale studies integrating the use of rodenticide and then fertility control are required.…”
Section: Fertility Controlmentioning
confidence: 99%
“…Liu J. et al's results reflect the need to directly assess the response of a species to a control agent that has been tested in several other species (Jacoblinnert et al 2022;Massei et al 2023). Sidhu and Singla (2023) showed that the consumption of quinestrol alone for 10 days by male lesser bandicoot rats, Bandicota bengalensis, in the laboratory reduced their fertility for more than 30 days, with partial reversibility by 60 days. A small-scale field assessment yielded promising results but further, more broad-scale studies integrating the use of rodenticide and then fertility control are required.…”
Section: Fertility Controlmentioning
confidence: 99%